Full genome ultra‐deep pyrosequencing associates G‐to‐A hypermutation of the hepatitis B virus genome with the natural progression of hepatitis B. Issue 12 (7th June 2013) - Beggel, B.; Münk, C.; Däumer, M.; Hauck, K.; Häussinger, D.; Lengauer, T.; Erhardt, A.
Summary: Human APOBEC3 (A3) cytosine deaminases are antiviral restriction factors capable of editing the genome the hepatitis B virus (HBV). Despite the importance of the human A3 protein family for the innate immune response little is known about the clinical relevance for hepatitis B. The aim of this study was to utilize ultra‐deep pyrosequencing (UDPS) data to analyse the phenomenon of G‐to‐A hypermutation of the complete HBV genome and to relate it to fundamental characteristics of patients with chronic hepatitis B. By analysing the viral population of 80 treatment naïve patients (47 HBeAg‐positive and 33 HBeAg‐negative), we identified an unequal distribution of G‐to‐A hypermutations across the genome. Our data indicate that G‐to‐A hypermutation occurs predominantly in a region between nucleotide positions 600 and 1800 a region which is usually single stranded in matured HBV particles. This implies that A3 likely edits HBV in the virion. Hypermutation rates for HBeAg‐negative patients were more than 10‐fold higher than those of HBeAg‐positive patients. For HBeAg‐negative patients higher hypermutation rates were significantly associated with the degree of fibrosis. Additionally, we found that for HBeAg‐positive chronic hepatitis G‐to‐A hypermutation rates were significantly associated with the relative prevalence of the G1764A mutation, which is related to HBeAg seroconversion. In total, our data imply an important association of hypermutation mediated by A3 deaminases with the natural progression of chronic hepatitis B infections both in terms of HBeAg seroconversion and disease progression towards cirrhosis.